4-Phenyl-1,2,3,4-tetrahydropyrimido[1,2-a]benzimidazol-2-one - Gong-Chun Li; Feng-Ling Yang; Chang-Sheng Yao (Acta Crystallographica Section E, 2008)
In the title compound, C16H13N3O, the tetrahydropyrimidinone ring adopts a sofa conformation. In the crystal structure, molecules are linked by N—H...N hydrogen bonds and C—H...π interactions.